Design and Development of an Affordable Anthropomorphic Hand Prosthesis - Bicho, Murilo C.; Kappel, Kristofer S.; Drews-Jr, Paulo L. J.; Guerra, Rodrigo S. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2025: Anais do XVII Simpósio Brasileiro de Robótica e XVI Workshop de Robótica na Educação, 2025)
This work aims to develop an open-source anthropomorphic hand prosthesis. The methodology involves designing a manipulator that replicates the precision grips of the human hand. The development process integrated CAD modeling and 3D printing for prototyping a biomimetic structure that combines a reinterpretation of organic anatomy with practical functionalities in a synthetic design. The prosthesis features 22 degrees of freedom, actuated by N20 motors controlled through shift registers and motor drivers, with joint position feedback provided by resistive sensors. The embedded firmware running on an ESP32 microcontroller utilizes an on-off control strategy with a dead zone to achieve accurate joint positioning. Experimental tests demonstrate the system's ability to perform various grasp types and manipulate small objects, highlighting its potential applications in assistive robotics and dexterous manipulation.